Implementasi PMK Nomor 66 Tahun 2023, Core Tax Administration System, dan Pemberian Fasilitas PPh 21 Ditanggung Pemberi Kerja Badan - Fahmi Setiadi; Asaprima Putra Karunia; Juliati Juliati; Titik Setyaningsih; Sri Suranta (Jurnal Akuntansi dan Pajak, 2024)
The implementation of PMK Number 66 in the year 2023 and the Core Tax Administration System are tax reformations to avoid tax avoidance behavior. This tax reform changed the way of a company for giving the income tax PPh 21 compensation to the employee. After the implementation of this PMK, the company can’t use the net method for giving the income tax PPh 21 compensation. This research shows that the implementation of a gross-up method for giving the income tax PPh 21 compensation that is suitable by the implementation of the PMK Number 66 in the year 2023 gives a lower expense for the company than the net method, especially for the company that the majority of employee income tax tariff at 5% and 15% level. The gross-up method also gives a lower tax risk for the employee and company, especially for facing the implementation of the Core Tax Administration System